2010
DOI: 10.1088/0957-0233/21/2/025202
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic for quantifying heat flux from a thermite spray

Abstract: Characterizing the combustion behaviors of energetic materials requires diagnostic tools that are often not readily or commercially available. For example, a jet of thermite spray provides a high temperature and pressure reaction that can also be highly corrosive and promote undesirable conditions for the survivability of any sensor. Developing a diagnostic to quantify heat flux from a thermite spray is the objective of this study. Quick response sensors such as thin film heat flux sensors cannot survive the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Here, net retained masses of between 11 and 52 % have been observed with heating efficiencies of 4.4 to 42.4 % calculated when using glass substrates. Nixon et al [48] reported 10-17 % heating efficiency; however, they were heating a substrate with the directed flame from thermite rather than burning the thermite on the substrate, which isn't comparable to the present work. Crane et al [41] burned thermite powders on a steel substrate and measured heat transfer efficiencies between 4.6 and 52 %.…”
Section: Heat Production and Retentioncontrasting
confidence: 84%
“…Here, net retained masses of between 11 and 52 % have been observed with heating efficiencies of 4.4 to 42.4 % calculated when using glass substrates. Nixon et al [48] reported 10-17 % heating efficiency; however, they were heating a substrate with the directed flame from thermite rather than burning the thermite on the substrate, which isn't comparable to the present work. Crane et al [41] burned thermite powders on a steel substrate and measured heat transfer efficiencies between 4.6 and 52 %.…”
Section: Heat Production and Retentioncontrasting
confidence: 84%
“…Ignition ports are positioned to allow for the nichrome wire to enter the acrylic cup and allow for clearance from the nozzle. The angle of the nozzle has been tested, and results show that the energy of the spray is maximized at 45° from the centerline (see Figure b) . The material used for the nozzle, body, and end plug is grade G10/FR4 Garolite from McMaster-Carr.…”
Section: Methodsmentioning
confidence: 99%
“…Quantifying the energy from thermite combustion impingent upon a substrate has only recently been documented by Nixon et al They engineered a heat flux sensor that could withstand the high temperature and corrosive nature of a thermite spray. Using a series of probes (each fitted with thermocouples), the temperature was measured and the heat flux was calculated for an Al + CuO reaction spray impingent on the sensor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations